2002
DOI: 10.1002/ijc.10704
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal alterations in small cell lung cancer revealed by multicolour fluorescence in situ hybridization

Abstract: Small cell lung cancer (SCLC) is a major cause of cancer related morbidity and mortality. Karyotypic studies have revealed numerous chromosomal aberrations in most SCLC however, classical G-banding analysis is unable to fully characterise complex marker chromosomes. Recent developments in molecular cytogenetics now allow accurate identification of the chromosomal components of complicated rearrangements. We have applied the technique of multicolour fluorescence in situ hybridization (M-FISH) in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 16 publications
1
9
1
1
Order By: Relevance
“…G, interphase FISH using centromeres 3 (red), 7 (green), 17 FISH of the original tumor showed that its ploidy status was the same as that of the engraftments and confirmed CGH findings. Finally, the squamous cell carcinoma, LU16-SQCC, also showed a complex karyotype consistent with findings from other cytogenetic descriptions of SQCCs (23). FISH analysis of the original tumor specimen was consistent with the SKY findings in the xenograft, specifically, the detection of two copies of 9p21 in the original specimen corresponding to the clonal loss of 9p in one of the three chromosome 9 homologues.…”
Section: Lu13-cas Tumor Before Graftsupporting
confidence: 86%
“…G, interphase FISH using centromeres 3 (red), 7 (green), 17 FISH of the original tumor showed that its ploidy status was the same as that of the engraftments and confirmed CGH findings. Finally, the squamous cell carcinoma, LU16-SQCC, also showed a complex karyotype consistent with findings from other cytogenetic descriptions of SQCCs (23). FISH analysis of the original tumor specimen was consistent with the SKY findings in the xenograft, specifically, the detection of two copies of 9p21 in the original specimen corresponding to the clonal loss of 9p in one of the three chromosome 9 homologues.…”
Section: Lu13-cas Tumor Before Graftsupporting
confidence: 86%
“…Mutations and amplifications in the epidermal growth factor receptor (EGFR) kinase domain were shown to correlate with the response to erlotinib and gefitinib (6,(11)(12)(13)(14). Unfortunately, no such progress has been achieved with SCLC, although genomic analysis of SCLC has been reported (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regions on this chromosome arm have been implicated in SCLC and non-small-cell lung cancer (NSCLC) (Girard et al, 2000;Nomoto et al, 2000;Chizhikov et al, 2001;Ashman et al, 2002). Here, we describe the construction of a unique resource for analysing 1p.…”
mentioning
confidence: 99%